Influence of load dosage in testing on lactate threshold identification - Stasiulis, A. (Education. Physical training. Sport, 1998)
The aim of the study was to investigate how the lactate threshold (LaTh) identification possibility when heart rate (HR) during increasing intermittent exercise is analysed depends on work interval duration or type of increase. 8 men basketball players performed intermittent gradually increasing exercise on the cycle ergometer. Each subject was tested three times. During two testings the work load was increased stepwisely, and the duration of each work interval was two or three min. During the third testing every work load was reached gradually during the 1.5 min by the subject. The duration of the passive rest intervals always was 5 min. The ECG was continuously recorded. The LaTh was determined from the relationship of HR during rest intervals to work load performed. The LaTh was either determined visually according to the curve pattern or using linear regression analysis according to the intersection point of two best fitting lines. Results showed that the value of LaTh determined from the recovery HR relationship to work load during increasing intermittent exercise neither depends on the pattern of successive work load increase nor on the work load duration (2 or 3 min). No statistically significant difference between LaTh identified visually or by linear regression analysis was observed.